2019
DOI: 10.1177/0269216319845804
|View full text |Cite
|
Sign up to set email alerts
|

Implementing advance care planning with community-dwelling frail elders requires a system-wide approach: An integrative review applying a behaviour change model

Abstract: Background: Facilitating advance care planning with community-dwelling frail elders can be challenging. Notably, frail elders’ vulnerability to sudden deterioration leads to uncertainty in recognising the timing and focus of advance care planning conversations. Aim: To understand how advance care planning can be better implemented for community-dwelling frail elders and to develop a conceptual model to underpin intervention development. Design: A structured integrative review of relevant literature. Data sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 79 publications
3
52
0
Order By: Relevance
“…Covid-19 guidance on advance care planning has largely focused on its product: a plan recording an individual’s treatment preferences 34. Yet evidence suggests that some of the main benefits that frail patients and their loved ones experience from advance care planning are strengthened relationships with each other and their clinical teams, and support through the experiences of living and dying with frailty and bereavement 6789. These benefits come largely from the conversations that constitute the planning process, particularly when these occur over time and include the patient’s family and loved ones.…”
Section: Process Versus Productmentioning
confidence: 99%
See 2 more Smart Citations
“…Covid-19 guidance on advance care planning has largely focused on its product: a plan recording an individual’s treatment preferences 34. Yet evidence suggests that some of the main benefits that frail patients and their loved ones experience from advance care planning are strengthened relationships with each other and their clinical teams, and support through the experiences of living and dying with frailty and bereavement 6789. These benefits come largely from the conversations that constitute the planning process, particularly when these occur over time and include the patient’s family and loved ones.…”
Section: Process Versus Productmentioning
confidence: 99%
“…Research has investigated the experiences and priorities of frail and older people in planning their care 7891114. However, few attempts have been made to collaborate with patients and their loved ones to design approaches to meet their needs 89. Thus translating evidence about patients’ priorities into best practice remains largely a matter of clinical expertise.…”
Section: Process Versus Productmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, successful ACP programs require a crosssectoral, multidisciplinary approach, which implies improved communication even among all healthcare providers [15]. Studies from other countries have shown that ACP can reduce distress, depression and anxiety not only in residents but also in significant others and care staff [16,17].…”
Section: Backgoundmentioning
confidence: 99%
“…Younger patients may need broad ACP education while elderly patients, especially those who are frail will have higher acuity and urgency for ACP. [30] The EMR is a tool to facilitate ACP by providing easy identification of patients without advance directives and documentation of ACP conversations and decisions. A review of the utility of the EMR in ACP showed its most common uses are establishing documentation templates, creating electronic order sets, and automated prompts to trigger ACP discussions.…”
Section: Successful Acp Implementation In Healthcare Systemsmentioning
confidence: 99%